ZISWAHIB Processing Website Design (Zakat, Infaq, Alms, Waqf, Grants) at the North Sumatra Branch of Orphans House Using the Bootstrap Framework V.5.1.3 - Batubara, Muhammad Zulpan; Putri, Raissa Amanda (International Conference on Sciences Development and Technology, 2021)
Era 4.0 is the era of human digitization in the development of technology and information, ease of access and ease of obtaining information are advantages for many people. Not only used for individuals but technology and information can be used to support the needs of an agency, institution, or company. Like a website that is equipped with a database, the website will be useful for storing data or being able to view data that has been saved. Information systems can not only be used for large companies or agencies, all companies must have an information system to speed up the work of the employees of the company or agency, moreover, the Orphan House is engaged in the socio-religious field. This research methodology uses a qualitative methodology with a system development method using the waterfall method. This website is built with bootstrap framework V.5.1.3. This website can make it easier for employees at Rumah Yatim to manage ZISWAHIB (Zakat, Infaq, Alms, Waqf, Grants) to work faster and more efficiently.